A critical study of alternative education provisions for young people aged 16 to 24 years in the United Kingdom. Issue 6 (3rd October 2022) - Paterson-Young, Claire; Denny, Simon
ABSTRACT: In the United Kingdom, the number of young people (16 to 24 years-old) not in education, employment or training (NEET) was estimated to be c.763, 000 in October to December 2019. The purpose of this paper is to explore the experiences of NEET young people attending alternative education provisions that focus on physical and mental health in promoting positive outcomes. Semi-structured interviews with young people ( n = 18), parents ( n = 10), and staff ( n = 8), analysed using Constant Comparative Method, were conducted in an alternative education provision in England and Wales. Analysis led to the identification of themes around motivation, empowerment, and confidence. The findings illustrate that young people in alternative education provisions benefit from an approach that placed health, well-being and confidence building at their core. This paper outlines the implications for policy-makers and practitioners in designing alternative education provisions with physical activity as part of the core curriculum.